China's Transboundary Groundwater Cooperation in the Context of Emerging Transboundary Aquifer Law. Issue 4 (10th May 2017) - He, Yanmei
Abstract: China shares more than 20 transboundary aquifers with its coaquifer states, but they have not exploited their transboundary groundwater resources, and these resources have not been governed by any international agreements. Given the close interaction between surface water and groundwater, and the growing demands for transboundary groundwater in China and its coaquifer states, there is increasing necessity for these countries to undertake international cooperation on this issue. This article overviews China's transboundary aquifers, reviews the duty to cooperate on China's transboundary groundwater as well as the emerging transboundary aquifer law. It concludes by providing some proposals on international cooperation in this context, based on the two theories of international water law—limited territorial sovereignty and common interests, taking into account the practicability of China's cooperation with its coaquifer states. The author suggests that China cooperates with its coaquifer states through such means as the exchange of data and information, joint monitoring, the conclusion of bilateral or multilateral aquifer agreements, the establishment of joint management mechanisms, and international technical cooperation. Abstract : Article impact statement : This article examines the necessity, feasibility, and means of China's transboundary groundwater cooperation from a multidiscipline.